The Value of Islamic Education on Layang Fasholatan and Its Relevance for Modin - Syahriyah, Ummi Ulfatus; Maknun, Moch. Lukluil; Islahuddin, Islahuddin; Iswanto, Agus; Dahri, Harapandi (UIN Maulana Malik Ibrahim Malang, 2025)
The discovery of manuscripts preserved by the community on the slopes of Mount Kawi, specifically in the village of Sumberdem, Wonosari, Malang, is significant and merits further exploration through content analysis. In addition to serving as evidence of the village’s identity as an Islamic proselytizing center, these manuscripts deserve to be studied and their contents revealed. One particularly noteworthy manuscript is Layang Fasholatan, which outlines concise guidelines on fiqh, akidah, and morals/tasawwuf that remain relevant in the present context. Its content can also be contextualized with the responsibilities of a village imam/modin, whose role includes leading religious rites such as weddings and funeral processions. Despite the breadth of prior research, few studies have specifically examined the practical relevance of manuscript content to the contemporary roles of village religious leaders such as the modin. This study offers a novel contribution by contextualizing the worship-related teachings in Layang Fasholatan within the lived religious duties of a modin in modern rural Java. Using a philological approach, content analysis, and in-depth interviews, this study presents a focused analysis of the manuscript, specifically within the scope of amaliyah/fiqh and worship. The manuscript provides a concise guide to funeral practices, prayer procedures, devotional supplications (wirid), and marriage contract guidelines. This study affirms that Layang Fasholatan, with its emphasis on worship practices, aligns closely with the religious functions and practical needs of a modin, making it both a historically and contemporarily valuable resource. While the research effectively utilizes philological and content analysis methods, it remains a preliminary exploration focused solely on the amaliyah aspect, leaving ample opportunity for future studies to examine its other dimensions and broader applications. Penemuan manuskrip-manuskrip yang dilestarikan oleh masyarakat di lereng Gunung Kawi, tepatnya di Desa Sumberdem, Kecamatan Wonosari, Kabupaten Malang, merupakan temuan yang signifikan dan layak untuk diteliti lebih lanjut melalui kajian isi. Selain menjadi bukti identitas desa sebagai kawasan dakwah Islam, manuskrip-manuskrip ini perlu dikenali dan diungkapkan isinya. Salah satu manuskrip yang menarik untuk dikaji adalah Layang Fasholatan, yang memuat panduan singkat mengenai fikih, akidah, dan akhlak/tasawuf yang masih relevan dalam konteks kekinian. Isi manuskrip ini juga dapat dikontekstualisasikan dengan tugas seorang imam atau modin desa, yang berperan memimpin pelaksanaan ibadah masyarakat, khususnya dalam prosesi pernikahan dan kematian. Meskipun telah banyak penelitian sebelumnya, sedikit yang secara khusus menelaah relevansi praktis isi manuskrip terhadap peran kontemporer tokoh agama desa seperti modin. Studi ini memberikan kontribusi baru dengan mengontekstualisasikan ajaran-ajaran ibadah dalam Layang Fasholatan ke dalam praktik keagamaan sehari-hari seorang modin di pedesaan Jawa modern. Dengan menggunakan pendekatan filologis, analisis isi, dan wawancara mendalam, studi ini menyajikan analisis terbatas terhadap isi manuskrip dalam lingkup amaliyah/fikih dan ibadah. Manuskrip ini memberikan panduan ringkas mengenai tata cara pemulasaraan jenazah, tata cara salat, wirid dan doa, serta panduan akad nikah. Studi ini menegaskan bahwa Layang Fasholatan, dengan penekanan pada praktik ibadah, sangat selaras dengan kebutuhan religius dan fungsi seorang modin, menjadikannya sumber yang berharga dan praktis baik dalam konteks historis maupun kekinian. Meskipun penelitian ini telah berhasil menerapkan metode filologis dan analisis isi secara efektif, studi ini masih merupakan eksplorasi awal yang hanya berfokus pada aspek amaliyah, sehingga masih terbuka peluang besar bagi penelitian lanjutan untuk mengkaji dimensi lainnya dan penerapan yang lebih luas.